MICROBIAL ASSESSMENT OF PRE-PACKAGED FOOD - PRACHI CHAUDHARY; SHELZA BANYAL; VIKAS BENIWAL; VARSHA SINGH (International Journal of Pharma and Bio Sciences, 2014)
The present study was conducted to check the microbiological safety of pre-packaged foods during January 2011 to April 2011. A total of 30 randomly collected samples from retail outlets were subjected for presence of microorganisms and total viable count. Out of 30 samples 28 (93.2%) showed the growth, Total Viable count ranged from 4 x 102 to 2.5 x 107 CFU/g. Among positive samples 57.14% were Gram-positive organisms, 35.70% Gram-negative organisms while 7.14% fungus i.e. Candida. Amongst Gram negative organisms maximum isolates were of E. coli 70% , 10% Pseudomonas sp. & 20% Klebsiella sp. ,while Staphylococcus aureus 18.75% was the predominant Gram positive pathogen followed by Streptococci sp. 6.25%. The presence of potential pathogens in food samples reveals the need of accomplishment of quality control measures in marketing to improve public health risk.